25th Anniversary Article: CVD Polymers: A New Paradigm for Surface Modifi cation and Device Fabrication. (25th September 2013) - Coclite, Anna Maria; Howden, Rachel M.; Borrelli, David C.; Petruczok, Christy D.; Yang, Rong; Yagüe, Jose Luis; Ugur, Asli; Chen, Nan; Lee, Sunghwan; Jo, Won Jun; Liu, Andong; Wang, Xiaoxue; et al.
Abstract Well‐adhered, conformal, thin (<100 nm) coatings can easily be obtained by chemical vapor deposition (CVD) for a variety of technological applications. Room temperature modification with functional polymers can be achieved on virtually any substrate: organic, inorganic, rigid, flexible, planar, three‐dimensional, dense, or porous. In CVD polymerization, the monomer(s) are delivered to the surface through the vapor phase and then undergo simultaneous polymerization and thin film formation. By eliminating the need to dissolve macromolecules, CVD enables insoluble polymers to be coated and prevents solvent damage to the substrate. CVD film growth proceeds from the substrate up, allowing for interfacial engineering, real‐time monitoring, and thickness control. Initiated‐CVD shows successful results in terms of rationally designed micro‐ and nanoengineered materials to control molecular interactions at material surfaces. The success of oxidative‐CVD is mainly demonstrated for the deposition of organic conducting and semiconducting polymers.